“I am a dog”, Verbal Taboo to Convince: Verbal Taboo to Convince - Jamal Nasution; Mulyadi Mulyadi (Randwick International of Education and Linguistics Science Journal, 2021)
In daily and informal situation, individuals use language to connect one another. This research is on taboo words used by people of Padang Bolak Language (PBL) in daily communication. This research is a qualitative descriptive where the research problem is what, how, and why taboo words appear and are used in daily conversation of PBL. The data was taken by recording technique and taking notes on the conversations of residents at the location in Poken Salasa Village, Portibi District, Padang Lawas Regency, North Sumatera Province. From 45 data, the frequent taboo word is anjing (7 times), kafir (13 times), bujang/bujak/bujas (19 times), haram (3 times), and murtad (3 times). The reasons of speaker using taboo words are various. The speaker utters dog to take an oath, to trust or to make others believe. The word kafir is the speaker’s way to take an oath and to convince others. The word bujang/bujak/bujas is used only among the intimate fellowship. Speaker’s expression of haram appears when he disagrees, be opposite to something, and doesn’t expect to one condition. Then murtad is uttered by speaker when he wants to trust other, makes an oath to support his statement. The next research is expected to expose the more reasons of using taboo words in psychological perspectives.